The American Musical and the Formation of National Identity - Knapp, Raymond (Book collections on Project MUSE., 2005)
Along with jazz & the American motion picture, the American musical is a distinctive art form that emerged in the first half of the 20th century. Raymond Knapp explores its origins & the themes that have dominated up to the modern day.